Refugia under threat: Mass bleaching of coral assemblages in high‐latitude eastern Australia. (31st August 2019) - Kim, Sun W.; Sampayo, Eugenia M.; Sommer, Brigitte; Sims, Carrie A.; Gómez‐Cabrera, Maria del C.; Dalton, Steve J.; Beger, Maria; Malcolm, Hamish A.; Ferrari, Renata; Fraser, Nicola; Figueira, Will F.; Smith, Stephen D. A.; et al.
Abstract: Environmental anomalies that trigger adverse physiological responses and mortality are occurring with increasing frequency due to climate change. At species' range peripheries, environmental anomalies are particularly concerning because species often exist at their environmental tolerance limits and may not be able to migrate to escape unfavourable conditions. Here, we investigated the bleaching response and mortality of 14 coral genera across high‐latitude eastern Australia during a global heat stress event in 2016. We evaluated whether the severity of assemblage‐scale and genus‐level bleaching responses was associated with cumulative heat stress and/or local environmental history, including long‐term mean temperatures during the hottest month of each year (SSTLTMAX ), and annual fluctuations in water temperature (SSTVAR ) and solar irradiance (PARZVAR ). The most severely‐bleached genera included species that were either endemic to the region ( Pocillopora aliciae ) or rare in the tropics (e.g. Porites heronensis ). Pocillopora spp., in particular, showed high rates of immediate mortality. Bleaching severity of Pocillopora was high where SSTLTMAX was low or PARZVAR was high, whereas bleaching severity of Porites was directly associated with cumulative heat stress. While many tropical Acropora species are extremely vulnerable to bleaching, the Acropora species common at high latitudes, such as A. glauca and A. solitaryensis, showed little incidence of bleaching and immediate mortality. Two other regionally‐abundant genera, Goniastrea and Turbinaria, were also largely unaffected by the thermal anomaly. The severity of assemblage‐scale bleaching responses was poorly explained by the environmental parameters we examined. Instead, the severity of assemblage‐scale bleaching was associated with local differences in species abundance and taxon‐specific bleaching responses. The marked taxonomic disparity in bleaching severity, coupled with high mortality of high‐latitude endemics, point to climate‐driven simplification of assemblage structures and progressive homogenisation of reef functions at these high‐latitude locations. Abstract : High‐latitude region has been heralded as potential climate change refugia for many species. However, our findings highlight that high‐latitude coral assemblages are critically threatened by the effects of ocean warming as endemic and high‐latitude specialist species are particularly prone to punctuated heat stress.